An environmental history of the world [ humankind's changing role in the community of life - Hughes, J. Donald [ (Johnson Donald)] , 1932- (London ; New York : Routledge, 2009)
This book is an overview of human history in relationship to the natural environment, from origins to the present, with case studies of different societies in each period.
1. Introduction : history and ecology -- 2. Primal harmony -- 3. The great divorce of culture and nature -- 4. Ideas and impacts -- 5. The Middle Ages -- 6. The transformation of the biosphere -- 7. Exploitation and conservation -- 8. Modern environmental problems -- 9. Present and future
Description based on print version record
This edition published in the Taylor & Francis e-Library, 2009
Includes bibliographical references and index
Keywords: Biotic communities -- History; Human ecology -- History; Nature -- Effect of human beings on -- History; Biotic communities; Human ecology; Nature